Effects of Brand- and Customer-Related Factors on Purchase Decision on Chinese Smartphone Brands in Thailand - Wongsawat, Chinnicha (Animo Repository, 2020)
In Thailand, the Chinese smartphone brands, such as Oppo, Vivo, and Huawei, seek to increase further their combined domestic market share of around 50% in the foreseeable future. Therefore, systematic data on the purchase decision among Thai customers on Chinese smartphone brands would be informative. This study discusses the effects of innovative products, marketing mix, customer preferences, and customer satisfaction on Thai customers’ purchase decision of Chinese smartphone brands. Data were drawn from a survey involving a randomly-selected sample of 600 Thais who had purchased a Chinese smartphone brand. Using SPSS 22.0 and LISREL 9.2, data were analyzed to ascertain the statistical significance and the extent of the effects of the four factors. Results suggest that innovative products, marketing mix, customer preferences, and customer satisfaction had statistically significant direct, indirect, and total effects on a purchase decision. Customer satisfaction and customer preferences were the top-tiered factors, whereas marketing mix and innovative products were the lower-tiered. Overall, customer satisfaction, customer preferences, marketing mix, and innovative products explained 58.0% of the variation in the purchase decision, whereas customer preferences, marketing mix, and innovative products explained 43.0% of the variation in customer satisfaction. To further increase their local market share, the Chinese brands have to continue addressing the preferences and satisfaction of domestic customers while recalibrating their brand strategies so that these become more impactful on the customers’ purchase decision. Research is needed in these areas.